FAKTOR-FAKTOR YANG MEMENGARUHI PENGAMBILAN KEPUTUSAN TRANSFER PRICING PERUSAHAAN - VEWI MARGARETH SIAHAAN; RUTJI SATWIKO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study is to present empirical evidence regarding the factors that influence Transfer Pricing decisions. These factors include Tunneling Incentive, Institutional Ownership, Exchange Rate, Profitability, Leverage, Tax avoidance, and Bonus Mechanism, where the dependent variable studied is Transfer Pricing. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange during 2021 to 2023. The sample in the study was selected using purposive sampling method, with a total sample of 79 manufacturing companies listed on the Indonesia Stock Exchange during 2021 to 2023. In analyzing the data, this study uses multiple regression methods. Based on the research results, it can be concluded that Leverage and Tax avoidance variables affect Transfer Pricing. While other independent variables such as Tunneling Incentive, Institutional Ownership, Exchange Rate, Profitability, and Bonus Mechanism have no effect on Transfer Pricing.